What matters to university students when looking for a rental house? - Kedin, Nor Adila; Saari, Izni Syamsina; Muhd Irpan, Hamidah; Ab Hamid, Ainon Syazana; Abdul Karim, Noor Ibtisam (UiTM Cawangan Johor, 2021)
The rapid growth of higher education institutions in Malaysia is parallel with the growing demand of its population pursuing tertiary education. For such reason, universities and other tertiary education providers are constantly challenged in providing sufficient in-campus accommodation to help students living comfortably. This opens the opportunity for homeowners who own rental units within proximity to a campus location to target students as their potential tenants.